(untitled) (Journal of Educational Sciences, 2016)
One of the main goals of higher education universities is is the formation of creative abilities of the future specialists relevant to the modern requirements. To this end, the authors propose the use of resources e-learning, and computer programs in the solution of physical problems in teaching physics, in particular in the practical classes. The majority of students majoring in physics have difficulty in solving physical problems, the choice of an efficient method of solution, to reveal the foundations of physical phenomenon regularities in solving various problems. With the purpose of simplifying this problem, the authors developed a computer model demonstration, experiment, and solve problems in physics. The article considers the methods of pplication of computer programs in solving physical problems in the process of learning physics.